Coupled Thermo-Hydro-Mechanical-Chemical Modeling of Permeability Evolution in a CO2-Circulated Geothermal Reservoir. (14th May 2019) - Tao, Jing; Wu, Yu; Elsworth, Derek; Li, Pan; Hao, Yang
Abstract : The meager availability of water as a heat transfer fluid is sometimes an impediment to enhanced geothermal system (EGS) development in semi-arid regions. One potential solution is in substituting CO2 as the working fluid in EGS. However, complex thermo-hydro-mechanical-chemical (THMC) interactions may result when CO2 is injected into the geothermal reservoir. We present a novel numerical model to describe the spatial THMC interactions and to better understand the process interactions that control the evolution of permeability and the heat transfer area. The permeability and porosity evolution accommodate changes driven by thermo-hydro-mechanical compaction/dilation and mineral precipitation/dissolution. Mechanical and hydraulic effects are demonstrated to exert a small and short-term influence on permeability change, while the thermal effects are manifest in the intermediate and short-term influence. The most significant and long-term influence on permeability change is by chemical effects, where decreases in fracture permeability may be of the order of 10 -5 due to calcite precipitation in fracture throats, which causes the overall permeability to reduce to 70% of the initial permeability. The initial pressure and temperature of the injected CO2 exerts an overriding influence on permeability. In particular, an increased temperature reduces the mineral precipitation in the fracture and enhances mineral dissolution within the matrix and pore but results in mechanical closure of the fractures. Optimizing injection pressure and temperature may allow the minimization of precipitation and the maximization of heat recovery.